GLOBAL AND INNOVATIVE TOOLS IN ENGLISH LANGUAGE LEARNING: STRENGTHS OR THREATS? - Žegunienė, Vaida; Karczewska, Małgorzata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article aims to reveal and present the essence of English language learning/teaching modernization via the innovative and globally used methods or tools. Innovations cannot be created and used without the existence of the traditional methodology and conventional activities. Positive experience in traditional education can be modified integrating global ideas. There are many alternatives in innovative tools usage; teachers and students are not limited with their own decisions and possibilities provided. Still, an important issue exists regarding positive and negative effects of such innovative and global tools on learners. Do participants of the study process demonstrate clear perception of possible benefits or reject such innovations due to their disadvantages? The survey reveals the current situation, where innovative tools do not exist independently. The usage of computer games, songs, films, social media (social networks, Youtube, the Internet) is not clearly separated from the traditional tools as books, friends, travelling or meeting foreigners. An in-depth overview gives basis for further studies on the application of more innovative tools, such as interactive activities on the Internet, interactive boards/tables, blogs, forums, virtual learning environments, strategies proposed by the scientists as neuroprogramming, language coaching, etc.